Connexin 43 reboots meiosis and reseals blood‐testis barrier following toxicant‐mediated aspermatogenesis and barrier disruption. Issue 4 (17th December 2015) - Li, Nan; Mruk, Dolores D.; Mok, Ka‐Wai; Li, Michelle W. M.; Wong, Chris K. C.; Lee, Will M.; Han, Daishu; Silvestrini, Bruno; Cheng, C. Yan
Abstract : Earlier studies have shown that rats treated with an acute dose of 1‐(2, 4‐dichlorobenzyl)‐1H‐indazole‐3‐carbohydrazide (adjudin, a male contraceptive under development) causes permanent infertility due to irreversible blood‐testis barrier (BTB) disruption even though the population of undifferentiated spermatogonia remains similar to normal rat testes, because spermatogonia fail to differentiate into spermatocytes to enter meiosis. Since other studies have illustrated the significance of connexin 43 (Cx43)‐based gap junction in maintaining the homeostasis of BTB in the rat testis and the phenotypes of Sertoli cell‐conditional Cx43 knockout mice share many of the similarities of the adjudin‐treated rats, we sought to examine if overexpression of Cx43 in these adjudin‐treated rats would reseal the disrupted BTB and reinitiate spermatogenesis. A full‐length Cx43 cloned into mammalian expression vector pCI‐neo was used to transfect testes of adjudin‐treated rats versus empty vector. It was found that overexpression of Cx43 indeed resealed the Sertoli cell tight junction‐permeability barrier based on a functional in vivo assay in tubules displaying signs of meiosis as noted by the presence of round spermatids. Thus, these findings suggest that over‐expression of Cx43 reinitiated spermatogenesis at least through the steps of meiosis to generate round spermatids in testes of rats treated with an acute dose of adjudin that led to aspermatogenesis. It was also noted that the round spermatids underwent eventual degeneration with the formation of multinucleated cells following Cx43 overexpression due to the failure of spermiogenesis because no elongating/elongated spermatids were detected in any of the tubules examined. The mechanism by which overexpression of Cx43 reboots meiosis and rescues BTB function was also examined. In summary, overexpression of Cx43 in the testis with aspermatogenesis reboots meiosis and reseals toxicant‐induced BTB disruption, even though it fails to support round spermatids to enter spermiogenesis.—Li, N., Mruk, D. D., Mok, K.‐W., Li, M. W. M., Wong, C. K. C., Lee, W. M., Han, D., Silvestrini, B., Cheng, C. Y. Connexin 43 reboots meiosis and reseals blood‐testis barrier following toxicant‐mediated aspermatogenesis and barrier disruption. FASEB J. 30, 1436–1452 (2016). www.fasebj.org